Migration of a Research Library's ICT-Based Services to a Cloud Platform. - Jayakanth, Francis; Byrappa, Ananda T.; Minj, Filbert (Information Technology & Libraries, 2022)
Libraries have been at the forefront in adopting emerging technologies to manage the library's operations and provide information services to the user community they serve. With the emergence of cloud computing (CC) technology, libraries are exploring and adopting CC service models to make their own services more efficient, reliable, secure, scalable, and cost-effective. In this article, the authors share their experience migrating some of the library's locally hosted ICT-based services onto the Microsoft Azure cloud platform. The migration of services to a cloud platform has helped the library significantly reduce the downtime of its services due to power or network or system outages.